The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1093/jac/dkaa254
|View full text |Cite
|
Sign up to set email alerts
|

Bone density, microarchitecture and tissue quality after 1 year of treatment with dolutegravir/abacavir/lamivudine

Abstract: Background Bone mineral density (BMD) decreases with ART initiation with a tenofovir disoproxil fumarate-containing regimen, although bone tissue quality increases. The impact of dolutegravir (DTG)/abacavir (ABC)/lamivudine (3TC)-based ART initiation on bone health parameters is not clear. Objectives To study the impact of DTG/ABC/3TC-based therapy on bone health parameters in ART-naive individuals with HIV after 48 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Similarly, after switching from a triple therapy including TDF in virologically suppressed PLWH with low BMD -1.0 T-score at weeks 24 and 48, raltegravir in combination with a boosted PI has also been linked to a significant rise in BMD at both the spine and hip ( 20 ). Similar results have been reported with BIC ( 18 ) or DTG ( 10 ). Consequently, TDF is the most likely responsible of the changes in bone quality reported in this study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similarly, after switching from a triple therapy including TDF in virologically suppressed PLWH with low BMD -1.0 T-score at weeks 24 and 48, raltegravir in combination with a boosted PI has also been linked to a significant rise in BMD at both the spine and hip ( 20 ). Similar results have been reported with BIC ( 18 ) or DTG ( 10 ). Consequently, TDF is the most likely responsible of the changes in bone quality reported in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, we found that the switch to a TAF regimen was associated with a significant improvement of bone quality of 5%. This increase is similar to those observed in naïve HIV individuals that start ABC-3TC-based regimen (10) or TDF-based regimen (9).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, it is unclear whether this is due to cessation of TDF or positive effects of ABC and DTG. PLWH initiating ABC ( 13–15 ) or DTG ( 16 ) lose BMD, but this could be due to the rapid rise in CD4+ cells post cART-mediated immune reconstitution. ( 17 ) ABC and DTG are not used in pre-exposure prophylaxis (PrEP), therefore their HIV-independent effects on bone are unknown.…”
Section: Introductionmentioning
confidence: 99%